The Best School in Jerusalem : Annie Landau's School for Girls, 1900-1960 - Schor, Laura S. (Book collections on Project MUSE., 2013)
Recounts the remarkable tenure of Annie Landau as principal of the Evelina de Rothschild School in Jerusalem.